Comparison of thermal performance between green roofs and conventional roofs - Marco A. Polo-Labarrios; Sergio Quezada-García; Heriberto Sánchez-Mora; M. Azucena Escobedo-Izquierdo; Gilberto Espinosa-Paredes (Case Studies in Thermal Engineering, 2020)
The present study compares the thermal performance of two buildings, one with a conventional roof and another with a green roof. In order to achieve this, a transient mathematical model is developed which considers the heat transfer through the walls and the roof, additionally the model considers the energy balance to determine the change of the temperature inside buildings. The mathematical model needs as input data, solar radiation, ambient temperature and wind speed, which are accessible meteorological variables. The results show that green roofs reduce inside temperature fluctuations of buildings up to 14 K, compared to conventional roofs. Additionally, green roofs allow reaching the comfort temperature: the temperature inside buildings is reduced up to 12 K for warm climates as Mexico City.